A ANALISA FAKTOR PERILAKU TERHADAP KEPATUHAN PENGUNAAN ALAT PELINDUNG DIRI PADA PETUGAS DI MASA PANDEMI COVID-19 - Ari Pratama Yudha; Dewi Rahayu; Ferizal Masra; Atikah Adyas (An Idea Health Journal, 2023)
The COVID-19 pandemic endangers everyone, especially Health Workers (Nakes) and Non Health Workers (Non Health Workers) who work in Health Service Health Facilities, Hospitals as health care facilities, can also be a source of infection. Hospital-acquired infections, otherwise known as nosocomial infections. To prevent nosocomial infections, a guideline is needed that aims to reduce the incidence of these infections, one of which is the use of Personal Protective Equipment (PPE). This study aims to determine the relationship between the determinants of the use of Personal Protective Equipment and to determine the effectiveness and workload of using PPE felt by workers at the Bandar Negara Husada Hospital during the COVID-19 pandemic. The design of this research is Crosssectional. The sample is 79 people. Data analysis used Chi-Square test and multiple logistic regression. The results of statistical analysis showed that there was a significant relationship between compliance with PPE use and knowledge (P=0.000), compliance with PPE use and availability (P= 0.018), compliance with PPE use with training (0.037) and compliance with PPE use with supervision (P= 0.000). Based on the multiple logistic regression test, it was found that the most dominant variable related to compliance with the use of PPE is knowledge (OR = 0.035) which means that officers with good knowledge of PPE are 0.35 times more obedient in using PPE than officers with poor knowledge.